Motivation to train during a pandemic: The role of fitness resources, mental health, and motivational profiles among student-athletes in team sports - Purc-Stephenson, Rebecca J.; Zimmerman, Thomas M. J.; Edwards, Rachel (Frontiers in Sports and Active Living, 2022)
The sporting season across post-secondary institutions was cancelled in March 2020 due to COVID-19, and student-athletes had to maintain their training at home. It is unclear what personal and contextual factors facilitated student-athletes’ ability to maintain their training routines at home when social distancing and lockdown (SD/L) policies were put in place. Our cross-sectional study of 433 student-athletes examined (a) how athletes adapted their training, (b) what training barriers they experienced, (c) whether motivational profiles were associated with differences in training behaviors and mental health, and (d) what variables predicted athletes’ motivation to train during this prolonged offseason. Student-athletes across Canada were recruited to complete an online survey between August and September 2020. Results showed that athletes significantly reduced their training load and intensity, with approximately 25% exercising two or fewer days a week. Barriers to training included limited access to fitness resources and equipment, having inconsistent training schedules, and experiencing emotional distractions, with some of these barriers more common among female athletes than male athletes. For motivation profiles, athletes with higher levels of intrinsic motivation tended to maintain the intensity of their workouts and experienced lower mood disturbance. A hierarchical multiple regression revealed that being male, being younger, having higher levels of intrinsic and introjected motivation, having access to fitness resources, maintaining a steady training schedule, having fewer emotional distractions, and lower mood disturbance were significant predictors to being motivated to train during the pandemic. We discuss strategies coaches and trainers can implement to best support their student-athletes.